Osseointegrated Metallic Implants for Finger Amputees: A Review of the Literature. Issue 6 (7th May 2022) - Bregoli, Chiara; Biffi, Carlo Alberto; Morellato, Kavin; Gruppioni, Emanuele; Primavera, Matteo; Rampoldi, Michele; Lando, Mario; Adani, Roberto; Tuissi, Ausonio
Abstract: Digital trauma amputations and digital agenesis strongly affect the functionality and aesthetic appearance of the hand. Autologous reconstruction is the gold standard of treatment. Unfortunately, microsurgical options and transplantation procedures are not possible for patients who present contraindications or refuse to undergo transplantation from the toe (e.g. toe‐to‐thumb transplantation). To address these issues, osseointegrated finger prostheses are a promising alternative. The functional assessments registered during follow‐up confirmed the promising outcomes of osseointegrated prostheses in the treatment of hand finger amputees. This review outlines (a) a detailed analysis of osseointegrated finger metallic components of the implants, (b) the surgical procedures suggested in the literature, and (c) the functional assessments and promising outcomes that demonstrate the potential of these medical osseointegrated devices in the treatment of finger amputees. Abstract : Osseointegrated implants are promising solutions for the treatment of hand finger amputees: the improvements in the design solutions, surgical protocols are making the bone‐anchored technique an optimal alternative to standard microsurgical procedures. Osseointegrated implants restore osseoperception and increase the self‐confidence of the patient.